2004
DOI: 10.3121/cmr.2.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Atopy in Rural Children: Is Farming Protective?

Abstract: The prevalence of asthma and other atopic diseases has recently increased, especially in urban and modernized regions of the world. The majority of published prevalence surveys report that asthma and atopy are less common among children living in rural areas. While many exposures differ in rural and urban areas of the world, several recent studies have suggested that agricultural exposures in early childhood may decrease the risk of developing atopic disease. Livestock exposure, in particular, seems to be impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 47 publications
2
33
0
2
Order By: Relevance
“…Several European cohort studies focused on the association between farm-living and allergy and asthma in children, namely the European Allergy and Endotoxin (ALEX), the Prevention of Allergy Risk Factors of Sensitization in Children Related to Farming and Anthroposophic Lifestyle (PARSIFAL), and the multidisciplinary study to identify the genetic and environmental causes of asthma in the European community (GABRIEL). Evidence of lower incidence and prevalence of asthma, hay fever and atopic sensitization in children exposed to farming lifestyle has been extensively reported [84][85][86][87][88][89][90][91][92].…”
Section: Raw Milk and Protection Against Asthma And Allergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several European cohort studies focused on the association between farm-living and allergy and asthma in children, namely the European Allergy and Endotoxin (ALEX), the Prevention of Allergy Risk Factors of Sensitization in Children Related to Farming and Anthroposophic Lifestyle (PARSIFAL), and the multidisciplinary study to identify the genetic and environmental causes of asthma in the European community (GABRIEL). Evidence of lower incidence and prevalence of asthma, hay fever and atopic sensitization in children exposed to farming lifestyle has been extensively reported [84][85][86][87][88][89][90][91][92].…”
Section: Raw Milk and Protection Against Asthma And Allergiesmentioning
confidence: 99%
“…Ege and colleagues (2007) evaluated data from PASTURE cohort study and highlighted that maternal lifestyle during pregnancy, included the use of boiled or un-boiled farm milk, affects the production of fetal IgE, determined in cord blood at birth [99]. In contrast, later life exposures of children do not provide any protection or may exacerbate symptoms [89].…”
Section: Raw Milk and Protection Against Asthma And Allergiesmentioning
confidence: 99%
“…Results summarized in a recent review showed that children on farms, especially those with farm-animal contact, seemed to have a decreased risk for allergies possibly due to endotoxin exposures, whereas adult farmers' allergies were exacerbated by endotoxin exposures (as reviewed in ref. 52). Exposures on a farm are complex and often not mutually exclusive.…”
Section: Cancer Epidemiology Biomarkers and Prevention 1291mentioning
confidence: 99%
“…1 In epidemiologic studies, both factors were shown to be associated with a higher prevalence of allergic rhinitis and sensitization. [2][3][4][5][6][7][8][9][10][11] Part of the association between obesity and sensitization has been attributed to the increased production of the proinflammatory hormone leptin, released by adipocytes. Laboratory studies have shown that leptin not only is associated with a T H 1 response 12 but also augments the ovalbumin-induced IgE production in sensitized mice.…”
mentioning
confidence: 99%